Pasteurization as a tool to control the bio-burden in solid herbal dosage forms: A pilot study of formulating Ashoka tablets with an industrial perspective - Hulikal Basavarajaiah Pushpalatha; Kumar Pramod; Ramachandran Sundaram; Ramakrishnan Shyam (Wolters Kluwer Medknow Publications, 2014)
Irradiation and use of preservatives are routine procedures to control bio-burden in solid herbal dosage forms. Use of steam or pasteurization is even though reported in the literature, not many studies are available with respect to its application in reducing the bio-burden in herbal drug formulations. Hence, we undertook a series of studies to explore the suitability of pasteurization as a method to reduce bio-burden during formulation and development of herbal dosage forms, which will pave the way for preparing preservative-free formulations. Optimized Ashoka (Saraca indica) tablets were formulated and developed. The optimized formula was then subjected to pasteurization during formulation, with an aim to keep the microbial count well within the limits of pharmacopoeial standards. Then, three variants of the optimized Ashoka formulation - with preservative, without preservative and formulation without preservative and subjected to pasteurization, were compared by routine in-process parameters and stability studies. The results obtained indicate that Ashoka tablets manufactured by inclusion of the pasteurization technique not only showed the bio-burden to be within the limits of pharmacopoeial standards, but also exhibited the compliance with other parameters, such as stability and quality. The outcome of this pilot study shows that pasteurization can be employed as a distinctive method for reducing bio-burden during the formulation and development of herbal dosage forms, such as tablets.